Examining through the Financial Ratio Analyses over Turkish Football Clubs in terms of Sportive Success and Financial Structure : Example of Galatasaray and Fenerbahce - Cihan Ulun; Azmi Yetim (ümit doğan üstün, 2016)
The purpose of this study has been to examine two major incorporated Football Clubs in terms of sportive success and Financial structure in Turkey. These clubs are handled as statute of bussiness corporations. Sportive and financial outputs are quite important for the management succes of commercial nature of bussiness corporation. The accuracy of sportive and financial analyses is crucial in sportive corporation. For this reason, financial ratio analysis are used in context(extent) of management science. Thus, the analysis focus on Galatasaray and Fenerbahce which are most successful footbal clubs national and international sportive success in Turkey. To results of the study, Galatasaray is more successful as a football club which won the championship three times at last five season than Fenerbahce which won two times at last five season in Turkey. At the same time, according to the ranking of UEFA, Galatasaray have en edge over fb through showing %29.35 success difference ratio. According to observation of liqudity ratio, "Cash ratio" is min 0.20, "Current Ratios" is higher than 1-1.5 are the prefered values for financial analysis ratio. Although accepted leverage ratio value is 0.50 from perspective of financial structure, this ratio is accepted 0.60 in Turkey. As regard to the consequences of financial analysis, sample clubs have lower Cash and Current Ratios than expected. However, in terms of financial structure, results are found higher than supposed to be. The results of this study shows that financial structure of the sample clubs are quite risky